Response of Soil Respiration and Its Components to Precipitation Exclusion in Vitex negundo Var. Heterophylla Shrubland of the Middle Taihang Mountain in North China - Shen, Huitao; Zhang, Lingkai; Meng, Henan; Zheng, Zhenhua; Zhao, Yanxia; Zhang, Tao (Frontiers in Environmental Science, 2021)
Assessing the response of soil heterotrophic and autotrophic respiration to climate change is critical for forecasting terrestrial carbon cycle behavior in the future. In the present study, we conducted a drought experiment in Vitexnegundo var. heterophylla shrub ecosystem of the Middle Taihang Mountain. Three precipitation manipulation treatments (natural conditions/ambient precipitation (CK), reduced precipitation by 30% (PE30), and reduced precipitation by 60% (PE60)) were used to study the impact of different levels of precipitation exclusion on total soil respiration (Rs) and its heterotrophic (Rh) and autotrophic (Ra) components. Our results showed that the rates of Rs and its components were significantly decreased under the precipitation exclusion treatments. The proportion of Rh in Rs reduced from 72.6 % for CK to 71.9 % under PE60. The annual cumulative C fluxes of Rs decreased by 47.8 g C m-2 in PE30 and 106.0 g C m-2 in PE60, respectively. An exponential relationship was observed between the rate of each soil respiration component and soil temperature in all treatments (P < 0.01). Moreover, each soil respiration component rate was better represented by a quadratic model which included soil moisture (P < 0.01). However, including both of soil temperature and soil moisture did not explain more variation in soil respiration components compared than the regression model with soil moisture only. In addition, excluding precipitation increased the temperature sensitivity (Q10 values) of Rs and its Ra and Rh components compared to the control. Collectively, our findings suggest that increased drought will inhibit the release of carbon from the soil to the atmosphere, and will likely decrease the contribution of Rh to Rs in this semiarid shrubland ecosystem.